ASSESSMENT OF FOOT DEFORMITY IN PRE-SCHOOL CHILDREN IN "ALADIN" KINDERGARTEN TUZLA - Almir Atiković,; Selma Kikanović,; Jasmin Bilalić,; Jasmin Zahirović,; Alen Gligić,; Almira Zukić,; Benjamin Gligić, (Sport Scientific And Practical Aspects, 2025)
The preschool years are characterized by additional physical development changes, enhanced motor abilities, and strengthened movement apparatus in the kid. The feet undergo morpho-functional changes at that period, particularly between the ages of 3 and 6, which result in the development of their longitudinal and transverse arches. The aim of this study was to evaluate the actual causes of foot deformity and its degree of severity in preschool-aged children, as well as the distinction in deformity representation between the sexes. The "Institution for preschool education" kindergarten "Aladin" in Tuzla is the focus of this study, which involves 74 children of both sexes, ages 3-6, were measured in 2023. Foot deformities are equally present in girls and boys. Deformities in boys are particularly pronounced: pedes recti 21 (56.8%), pedes planovalgi 6 (16.2%), while in girls: pedes recti 20 (54.1%), pedes excavati 8 (21.6%). With the Chi-square test, we determined the statistical significance of the presence of foot deformities between the sexes. By looking at the size of the chi-square (Pearson Chi-Square) 5.964a and Asymp. Sig. (2-sided) .544 tells us that there is no statistically significant difference in the representation of foot deformities between the sexes and that these deformities are equally represented. Because foot deviations can lead to problems kindergarten kids' foot arches need to be continuously monitored. This allows for timely intervention and the adoption of suitable treatment procedures to avoid the development of deformities.